Dosimetric And Geometric Accuracy Of Image Guided Intensity Modulated Radiotherapy (IG-IMRT) In Head And Neck Cancer Patients - M Zamri, Nada' Alia (2019)
Advances in radiotherapy technology has made it possible to deliver highly conformal Intensity Modulated Radiotherapy (IMRT) beam to treat patient with improved setup accuracy using Image Guided Radiotherapy (IGRT). This retrospective study investigates the accuracy of IG-IMRT treatment for 25 head and neck cancer (HNC) patients in Advanced Medical & Dental Institute (AMDI), Universiti Sains Malaysia. An ionisation chamber array detector has been characterised and used for patient specific IMRT QA. The characterisation study shows the doses measured using ionisation chamber array detector were within 2% compared with the doses calculated from the treatment planning system (TPS). All 25 IMRT treatment obtained percentage pass rate ≥95% when 3%/3 mm gamma criteria were used. The geometrical accuracy of the treatment was also analysed based on setup errors measured using kV cone beam CT based-IGRT. A total of 231 pre-treatment CBCT imaging were acquired prior to treatment and compared to the reference CT. PTV margin of ≥3 mm in RL direction, SI direction and AP direction is required if no setup correction was performed. Offline setup protocols; NAL and eNAL were simulated on the setup errors recorded. The eNAL protocol recorded the smallest setup error in all three directions; which were 1.59 mm for RL direction, 2.13 mm for SI direction and 1.61 mm for AP direction. The impact of setup errors on dose distributions was also assessed on six HNC patients.